2006
DOI: 10.1111/j.1365-2214.2006.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between parent and child report of quality of life in children with attention‐deficit/hyperactivity disorder

Abstract: Although self-report is an important means of eliciting QOL data, in children with ADHD, given the discrepancies in this study between parent and child report, measuring both perspectives seems appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
121
4
9

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 40 publications
15
121
4
9
Order By: Relevance
“…When the HRQOL of ADHD children was assessed using the CHQ-PF50, the ES in psychosocial and family-related HRQOL domains were mostly smaller in a study with a non-clinical sample [25] compared to other investigations that used clinical samples [21][22][23][24]. This pattern may be explained through the bias that is associated with utilizing clinical samples (see below).…”
Section: Parent Ratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the HRQOL of ADHD children was assessed using the CHQ-PF50, the ES in psychosocial and family-related HRQOL domains were mostly smaller in a study with a non-clinical sample [25] compared to other investigations that used clinical samples [21][22][23][24]. This pattern may be explained through the bias that is associated with utilizing clinical samples (see below).…”
Section: Parent Ratingsmentioning
confidence: 99%
“…In addition, some of the psychosocial subscales not directly associated with the diagnostic criteria of the particular mental disorder were also compromised (e.g., ADHD: large ES in 'self-esteem' [21][22][23][24]) -a pattern that possibly emerged due to comorbid disorders [8; 21].…”
Section: Parent Ratingsmentioning
confidence: 99%
“…For example, children who survived cancer reported higher QoL than healthy children (De Clercq, De Fruyt, Koot, & Benoit, 2004), and children with ADHD rated their QoL significantly higher than their parents did (Klassen, Miller, & Fine, 2006). However, the subjectivity of the evaluation is intrinsic to the concept.…”
Section: Can We Rely On Children's Reports Of Their Qol?mentioning
confidence: 99%
“…The study of interinformant agreement and factors affecting it remain an important issue in examining children and adolescents. While there are many publications about parent-child agreement on children's quality of life in physical illnesses such as epilepsy [27], asthma [5], cystic fibrosis [11], cancer [20,24,28,29,32], juvenile idiopathic arthritis [2], oral, oro-facial problems [12], there are less in psychiatric illnesses [attention-deficit/ hyperactivity: 3,16] and in general population [6,26,31]. There are only a few that compare ill population to a healthy one in the same study [5,20,28] but their methodology varies greatly, thus making comparison and generalizability difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, however, psychiatric diagnosis was based only on symptom checklist and thus conclusions regarding specific illnesses are not justified. Klassen et al [16] investigated children with attention deficit/hyperactivity disorder and found that parents reported significantly worse QoL for four life domains (behavior, mental health, self esteem, and family cohesion) but better QoL for physical functioning while no difference was found between raters in domains like general health, family activities, and social life. No studies were found about QoL agreement in depressed child populations.…”
Section: Introductionmentioning
confidence: 99%